IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN MELALUI KEGIATAN TERINTEGRASI PEMBELAJARAN PPKn DI SMP AL-MASUDIYAH 1 SRESEH SAMPANG - Miftahul Jannah; Sugeng Sugeng; Risqi Hartiasih Soetomo (Jurnal Cendekia Pendidikan, 2025)
The crisis of discipline among secondary school students raises concerns about the decline in the sense of responsibility among the younger generation. This phenomenon is controversial because character education has not been fully integrated into school learning practices. This article highlights the paradigm shift in Pancasila and Citizenship Education (PPKn) towards integrated learning oriented towards strengthening discipline. This study aims to analyze the implementation of discipline character education through PPKn learning activities at Al-Mas'udiyah 1 Sreseh Sampang Junior High School as a solution to the weak internalization of student discipline values. A descriptive qualitative approach was used with observation, interview, and documentation techniques of teachers, principals, and students. The results of the study show a positive transformation in the formation of disciplinary character through active, reflective, and contextual learning strategies. However, time constraints, traditional methods, and the irrelevance of the material to students' real experiences are major obstacles. This article emphasizes the urgency of value-based pedagogical innovation and the need for school policies that are more adaptive to the learning needs of 21st-century discipline.